Desenvolvimento de comprimidos de vimpocetina associada a nanocápsulas poliméricas - Pinheiro, Patrícia Garcia (2016)
Vinpocetine is a derivative of the alkaloid vincamine, widely used for the treatment of cerebrovascular and cognitive disorders due to strong neuroprotective effect. Furthermore, Vinpocetine has also antioxidant, anti-inflammatory and antitumor effects. However, this drug has both low absorption and water solubility, limiting their clinical use. Nanostructures have been employed to increase the oral bioavailability of drugs. However, these systems can exhibit low stability during storage. In this sense, solid pharmaceutical dosage forms have been developed to minimize these problems, such as tablets. Tablets can be obtained by different methods, including the wet granulation, where there is the agglomeration of particles to form granules using a binder liquid. Hence, the objective of the present study was to develop tablets containing Vinpocetine (2,5 mg)-loaded ethylcellulose nanocapsules, using coconut oil (CO) or medium chain triglycerides (MCT) as the core, through the wet granulation, for increasing the oral bioavailability of this drug. Also, stability studies of tablets and experiments of in vitro drug release were performed. According to the results, the nanocapsule suspensions showed adequate physicochemical characteristics (138-157 nm; -11 a -18 mV) and high encapsulation efficiency. However, the suspensions were unstable after 30 days of storage. Thus, it is necessary to develop solid forms using these systems as intermediate products for the production of tablets by the wet granulation, acting as granulation liquid. The granules obtained showed suitable physico-chemical characteristics (drug content and mean diameter after resuspension in water) and adequate technological properties (angle of repose, Carr index and Hausner factor). The tablets developed from the granules showed low friability, disintegration time next to 1 minute, acceptable hardness (8 a 11 N), drug content close to 100%, average weight of 550 mg and thickness as expected. Stability studies of tablets showed no decrease in drug content after 90 days of storage. Different assays were performed (diffusion dialysis bags, reverse dialysis and dissolution/apparatus 2) to evaluate the in vitro Vinpocetine release from both suspensions and/or tablets, in phosphate buffer pH 6.8. The results demonstrate that the suspensions and tablets, containing the nanocapsules, exhibited controlled release of Vinpocetine as compared to the diffusion of free drug. Also, the tablets without nanostructures showed drug diffusion/dissolution slower than the nanotechnological tablets. The employed methodology can influence in the percentages of released drug. In view of this, it can be concluded that tablets containing Vinpocetine-loaded nanocapsules are promising systems for its controlled release.